Effect of gonadal steroid hormone levels during pubertal development on social behavior of adult mice toward pups and synaptic transmission in the rhomboid nucleus of the bed nucleus of the stria terminalis. (24th August 2019) - Fukui, Kiyoshiro; Uki, Haruka; Minami, Masabumi; Amano, Taiju
Highlights: Behavioral transition during puberty is mediated by ER and AR-signaling. E2 but not DHT enhances the probability of excitatory neurotransmitter release in the BSTrh. Synaptic maturation in the BSTrh correlates to the behavioral pattern. Abstract: Sexually immature male mice exhibit parenting behavior toward unfamiliar pups; however, the percentage of males that engage in infanticidal behavior gradually increases with age. We previously reported that excitatory synaptic transmission of the rhomboid nucleus of the bed nucleus of the stria terminalis (BSTrh), a brain region implicated in infanticidal behavior, is reinforced during pubertal development. However, it remains unclear how gonadal steroid hormones mediate this behavioral transition and neural plastic change during pubertal development. Here we revealed that administration of either 17β-estradiol (E2) or 5α-dihydrotestosterone (DHT) to gonadectomized mice during pubertal development induced infanticidal behavior in adulthood (about 7 weeks old). Next, we performed whole-cell patch clamp recording in the BSTrh to study the effect of gonadal steroid hormones on neural synaptic transmission. We found that E2 but not DHT administration during pubertal development considerably enhanced excitatory synaptic transmission in the BSTrh by increasing the probability of excitatory neurotransmitter release from the presynaptic terminalis. These data suggest that reinforcement of excitatory synaptic transmission by estrogen-receptor-dependent signaling in the BSTrh during puberty may contribute to the development of infanticidal behavior.